Prolonged restricted training, fixture congestion and player rotation: What the COVID-19 pandemic taught us about injury risk in professional collision sport. Issue 6 (June 2022) - Starling, Lindsay T.; McKay, Carly; Cross, Matt; Kemp, Simon; West, Stephen; Stokes, Keith A.
Abstract: Objectives: The COVID19-induced suspension of the 2019-20 professional England rugby union season resulted in players being exposed to an extended restricted training period, coupled with a congested match schedule once competition resumed. We assessed the impact of these changes on match and training injuries in the final 20-weeks of the season following competition resumption. Design: Epidemiological study. Methods: The 2019-20 season was compared to the previous three seasons (2016-19). Results: There was no significant difference in the mean incidence, severity and burden of training and match injuries in 2019-20 compared to 2016-19 period mean. The 2019-20 post-suspension mean match injury rate [77/1000 h (95%CIs [confidence intervals]: 67-89)] was comparable to the 2019-20 pre-suspension [93/1000 h (95%CIs: 85-101)] and significantly lower than the 2016-19 equivalent post-suspension period [97/1000 h (95CIs: 90-104) IRR [incidence rate ratio] 0.8 p=0.002]. In the 2019-20 season, there was a significantly higher rate of training injury post-suspension in comparison to pre-suspension [3.8/1000 h (95CIs: 3.3-4.4) vs 2.7/1000 h (95% CIs: 2.5-3.1) IRR 1.4 p=0.005]. There was no significant difference in the overall incidence, severity or burden of injuries sustained in fixtures with shorter (<6 days) turnarounds but there was a significantly higher burden of soft tissue injuries. Conclusions: This is the first study to assess the effect of restricted training on injury risk in collision sports. Players were at an increased risk of training injury when returning from the suspension, but 10-weeks of preparatory training meant the incidence of match injury was not higher when competition resumed.